2017
DOI: 10.1101/169185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VPS18 recruits VPS41 to the human HOPS complex via a RING-RING interaction

Abstract: The copyright holder for this preprint (which was . http://dx.doi.org/10.1101/169185 doi: bioRxiv preprint first posted online 2 ABSTRACT Eukaryotic cells use conserved multisubunit membrane tethering complexes, including CORVET and HOPS, to control the fusion of endomembranes. These complexes have been extensively studied in yeast, but to date there have been far fewer studies of metazoan CORVET and HOPS. Both of these complexes comprise six subunits: a common four-subunit core and two unique subunits. On… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…VPS41 S285P interacted with both VPS18 and VPS33A, but interaction of VPS41 R662* with the other HOPS subunits was strongly reduced ( Figure 3A and S5). Since interaction between VPS41 and VPS18 requires the presence of the C-terminal RING domains that is absent from VPS41 R662* ( Figure S1), these data are in agreement with present literature (42).…”
Section: Vps41 R662* Poorly Interacts With Other Hops Subunitssupporting
confidence: 93%
“…VPS41 S285P interacted with both VPS18 and VPS33A, but interaction of VPS41 R662* with the other HOPS subunits was strongly reduced ( Figure 3A and S5). Since interaction between VPS41 and VPS18 requires the presence of the C-terminal RING domains that is absent from VPS41 R662* ( Figure S1), these data are in agreement with present literature (42).…”
Section: Vps41 R662* Poorly Interacts With Other Hops Subunitssupporting
confidence: 93%
“…Consistent with this, it has been shown that Vps8 binds through both the RING domain and a disordered C-terminus to both Vps18 and Vps11 subunits (Hunter et al, 2017). Our hypothesis is that TgVps8, in addition to acting as a sorting factor for ROP/MIC proteins, delivers proteases (such as ASP3), which are involved in the processing of pro-proteins, to secretory organelles.…”
Section: Figuresupporting
confidence: 80%
“…Furthermore, we demonstrated that the endosomal accumulation of other subunits that are HOPS specific (Vps39), common to CORVET and HOPS (Vps18 and Vps11), or interacting with HOPS (CHC and CK3L) is severely compromised in Tgvps8 mutants. Consistent with this, it has been shown that Vps8 binds through both the RING domain and a disordered C‐terminus to both Vps18 and Vps11 subunits (Hunter et al, ). Our hypothesis is that TgVps8, in addition to acting as a sorting factor for ROP/MIC proteins, delivers proteases (such as ASP3), which are involved in the processing of pro‐proteins, to secretory organelles.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations